The Influence of Work Stress, Work-Life Balance, and Job Insecurity on Employee Job Satisfaction at Hotel 'AI' Bekasi - Ayyasy, Muhammad Yahya; Kasmir, Kasmir (Dinasti International Journal of Digital Business Management, 2025)
This study aims to investigate the effect of job stress on work-life balance, job insecurity, and job satisfaction, as well as to examine the intermediary roles of work-life balance and job insecurity in the connection between job stress and job satisfaction among employees of Hotel “AI” Bekasi. A quantitative method was used with Structural Equation Modeling (SEM) using Partial Least Squares (PLS). Samples were selected through purposive sampling from Hotel “Ai” Bekasi employees. Results indicate that job stress negatively impacts work-life balance and job satisfaction significantly; while positively affecting job insecurity. Furthermore, work-life balance has a positive impact on job satisfaction, whereas job insecurity negatively influences it. The findings also show that work-life balance and job insecurity significantly mediate the association between job stress and job satisfaction. This study emphasizes the importance of managing job stress and effective management strategies to enhance work-life balance, reduce job insecurity, and increase job satisfaction, thereby positively impacting service quality and hotel competitiveness